2022
DOI: 10.1073/pnas.2116757119
|View full text |Cite
|
Sign up to set email alerts
|

HYL1-CLEAVAGE SUBTILASE 1 (HCS1) suppresses miRNA biogenesis in response to light-to-dark transition

Abstract: The core plant microprocessor consists of DICER-LIKE 1 (DCL1), SERRATE (SE), and HYPONASTIC LEAVES 1 (HYL1) and plays a pivotal role in microRNA (miRNA) biogenesis. However, the proteolytic regulation of each component remains elusive. Here, we show that HYL1-CLEAVAGE SUBTILASE 1 (HCS1) is a cytoplasmic protease for HYL1-destabilization. HCS1-excessiveness reduces HYL1 that disrupts miRNA biogenesis, while HCS1-deficiency accumulates HYL1. Consistently, we identified the HYL1K154A mutant that is insensitive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Interestingly, the N-terminal of HYL1 was unaffected by the proteolytic cleavage as compared to the full length AtHYL1 ( Figure 5 B). This analysis supported the recent report where HCS1 protease is confirmed as the protease for HYL1-destabilization [ 20 ] that might have an action like that of trypsin proteases. The incubation of bacterially purified full length AtHYL1 and AtHYL1N with crude protein extracted as a source of proteases from Col-0 further proves the tryptic nature of these proteases.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, the N-terminal of HYL1 was unaffected by the proteolytic cleavage as compared to the full length AtHYL1 ( Figure 5 B). This analysis supported the recent report where HCS1 protease is confirmed as the protease for HYL1-destabilization [ 20 ] that might have an action like that of trypsin proteases. The incubation of bacterially purified full length AtHYL1 and AtHYL1N with crude protein extracted as a source of proteases from Col-0 further proves the tryptic nature of these proteases.…”
Section: Resultssupporting
confidence: 91%
“…Another recent study proposed that cytoplasmic HYL1 regulates miRNA-mediated mRNA translation repression in association with argonaute 1 (AGO1) and altered meristem program 1 (AMP1) [ 19 ]. Studies have also found that an unknown cytoplasmic protease has been involved in regulating HYL1 proteolysis [ 16 , 20 ]. A recent report suggested that HYL1-cleavage subtilase 1 (HCS1) is a cytoplasmic protease for HYL1 destabilization [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the dcl1-9 and hyl1-2 miRNA biogenesis mutants were hypersensitive to red light in the hypocotyl elongation assay ( Sun et al, 2018 ). Furthermore, if dark-grown Arabidopsis seedlings are de-etiolated (shifted to light), the DCL1, HYL1, and SE microprocessor proteins accumulate to high levels and the pri-miRNA levels of most miRNAs are enhanced ( Choi et al, 2020 ; Bhagat et al, 2022 ; Jung et al, 2022 ). The expression of microprocessor components is under complex regulation, for instance, altered transcription, phosphorylation, and protein stability all contribute to the increased HYL1 level during de-etiolation ( Choi et al, 2020 ; Sacnun et al, 2020 ; Bhagat et al, 2022 ; Jung et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, if dark-grown Arabidopsis seedlings are de-etiolated (shifted to light), the DCL1, HYL1, and SE microprocessor proteins accumulate to high levels and the pri-miRNA levels of most miRNAs are enhanced ( Choi et al, 2020 ; Bhagat et al, 2022 ; Jung et al, 2022 ). The expression of microprocessor components is under complex regulation, for instance, altered transcription, phosphorylation, and protein stability all contribute to the increased HYL1 level during de-etiolation ( Choi et al, 2020 ; Sacnun et al, 2020 ; Bhagat et al, 2022 ; Jung et al, 2022 ). However, high throughput miRNA sequencing (miRNA-seq) revealed that although pri-miRNA levels and microprocessor concentrations are increased during photomorphogenesis, the total miRNAome is only moderately altered ( Choi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%